Philosophical and Psychopathological Perspective of Exile: On Time and Space Experiences - Silva Rojas, Matías; Armijo Nuñez, Julio; Nuñez Erices, Gonzalo (Frontiers in Psychiatry, 2015)
This article addresses the experience of exile from an interdisciplinary perspective, philosophy and mainy psychiatry, trying to understand the experiences of both space and time that people who live in exile have. The main purpose is to try to understand the experience of exile by rehearsing a psychopathological perspective to address it, so it can help with the treatment of disorders that come with this experience. The latter without cloistering it to the psychologically insane. Furthermore, the article tries to exploit the experience and reflection of philosophers and thinkers who, being exiled themselves, tried to understand and explain this radical human experience.